The atp operon: nucleotide sequence of the region encoding the alpha-subunit of Escherichia coli ATP-synthase. - Gay, N J (1981)
Part of the atp (or unc) operon encoding the alpha, beta, gamma, delta, and epsilon subunits of Escherichia coli ATP-synthase has been cloned into the plasmid pACYC 184. The DNA coding for the largest of these proteins, the alphas subunit, has been sequenced by cloning into the bacteriophage M13 and sequencing with dideoxy nucleotide chain terminators. It comprises 1539 nucleotides corresponding to a protein of 513 amino acids.